Diagnostic Accuracy of Splenic Index Measued on Ultrasound for Noninvasive Diagnosis of Esophageal Varices Keeping Endoscopy as Gold Standard - Saira Zafar, Muhammad Jamil Akhtar, Tahir Qadeer Khan, Mehreen Fatima, Syed Amir Gilani, Umair Riaz Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: End stage chronic liver disease results in the growth of fibrous tissue, the disruption of hepatic architecture, and the formation of nodules, which interfere with liver function and contribute to portal hypertension. Esophageal varices might arise when blood flow through liver is impeded, most typically by scar tissue in the liver caused by liver disease. For high-risk EV diagnosis, endoscopy is the gold standard, but is not available at most health centres in our nation. In individuals at high risk of esophageal varices, performing endoscopies on a yearly or biannual basis can be difficult. We wish to conduct a noninvasive investigation to gather local evidence and to confirm the accuracy of splenic index determined by ultrasonography in detection of EVs. Objective: To find out diagnostic accuracy of splenic index measured by Ultrasound for noninvasive diagnosis of esophageal varices keeping endoscopy as gold standard. Material & Methods: It was cross sectional study done in Department of Medicine, Mayo Hospital, Lahore. July 2021 to March 2022 marked the beginning and end of the nine-month research period in this case study. After meeting the inclusion criteria 215 patients were enrolled. Patients were undergone ultrasonography for assessment of liver texture & spleen size. Splenic Index was calculated. Afterwards, patient undergoes endoscopy assessment by researcher himself. Patient was labeled positive or negative for EVs. All data was assessed and patient was confirmed as positive or negative for EVs. Results: The mean age of the patients was 51.80 years, 84(44.2%) patients were male and 106(55.8%) patients were females. The sensitivity, specificity, PPV, NPV and diagnostic accuracy of USG for detection of esophageal varices was 92.98%, 88.16%, 92.17%, 89.33% & 91.05% taking endoscopy as gold standard. Cut off value for splenic index was 800 cm³. Conclusion: From the findings of this study we may concluded that splenic index measured by Ultrasound for noninvasive diagnosis of esophageal varices is a useful tool with high diagnostic accuracy keeping endoscopy as gold standard. Keywords: Diagnostic Accuracy, Ultrasound, Splenic Index, Endoscopy, Esophageal varices